Analisis Penerapan Pendekatan Bottom Up Planning Pada Implementasi Program Kota Tanpa Kumuh di Kelurahan Pangkajene Kacamatan Maritengngae Kabupaten Sidrap - Sakaruddin Mandjarreki (Universitas Islam Negeri Alauddin Makassar, 2023)
This research focuses on analyzing the explanation of the bottom up planning approach to the implementation of the City Without Slums Program (KOTAKU) from the perspective of community empowerment. As a concept and movement, community empowerment has become a popular narrative, especially in relation to community development planning based on bottom up planning. One of the main national programs whose implementation adopts this approach is the KOTAKU Program. This research has descriptive-qualitative characteristics using a phenomenological approach. Informants for this research include; facilitator, Coordinator of Community Self-Reliance Institutions (LKM), Village Head, and a number of residents who are primary beneficiaries of the program selected by purposive sampling. Research data sources include primary data obtained through in-depth interviews, and secondary data obtained by searching for relevant references. Data was collected using observation, interviews and documentation methods. Data analysis techniques are carried out by means of data reduction, data presentation, and drawing conclusions The research results show that the bottom up planning approach is explained in program implementation in terms of a number of variables, namely; basic principles of the program, the community as an active subject of development, community authority in decision making, and gender issues involving women in the program.